Protein kinase C chimeras: catalytic domains of alpha and beta II protein kinase C contain determinants for isotype-specific function. - Walker, S D (1995)
Protein kinase C (PKC) is involved in the proliferation and differentiation of many cell types. In human erythroleukemia (K-562) cells, the PKC isoforms alpha and beta II play distinct functional roles. alpha PKC is involved in phorbol 12-myristate 13-acetate-induced cytostasis and megakaryocytic differentiation, whereas beta II PKC is required for proliferation. To identify regions within alpha and beta II PKC that allow participation in these divergent pathways, we constructed chimeras in which the regulatory and catalytic domains of alpha and beta II PKC were exchanged. These PKC chimeras can be stably expressed, exhibit enzymatic properties similar to native alpha and beta II PKC in vitro, and participate in alpha and beta II PKC isotype-specific pathways in K-562 cells. Expression of the beta/alpha PKC chimera induces cytostasis in the same manner as overexpression of wild-type alpha PKC. In contrast, the alpha/beta II PKC chimera, like wild-type beta II PKC, selectively translocates to the nucleus and leads to increased phosphorylation of the nuclear envelope polypeptide lamin B in response to bryostatin-1. Therefore, the catalytic domains of alpha and beta II PKC contain determinants important for alpha and beta II PKC isotype function. These results suggest that the catalytic domain represents a potential target for modulating PKC isotype activity in vivo.